Use of a fluidized bed combustor and thermogravimetric analyzer for the study of coal ignition temperature - ï¿½vila, Ivonete [UNESP]; Crnkovic, Paula M.; Luna, Carlos M.R. [UNESP]; Milioli, Fernando E. (Elsevier, 2017)
Ignition experiments with two bituminous coals were carried out in an atmospheric bubbling fluidized bed combustor (FBC) and a thermogravimetric analyzer (TGA). In the FBC tests, the rapid increase in O2, CO2, and SO2concentrations is an indication of the coal ignition. In the TGA technique, the ignition temperature was determined by the evaluation of the TGA curves in both combustion and pyrolysis processes. Model-Free Kinetics was applied and the coal ignition temperatures were associated with changes in the activation energy values during the combustion process. The results show the coal with the lowest activation energy also showed the lowest ignition temperature, highest values of volatile content and a higher heating value. The application of two different ignition criteria (TGA and FBC) resulted in similar ignition temperatures. The FBC curves indicated the high volatile coal ignites in the freeboard, i.e. during the feeding in the reactor, whereas the low volatile coal ignites in the bed. Finally, the physicochemical characteristics of the investigated coal types were correlated with their reactivities for the prediction of the ignition temperatures behaviors under different operating conditions as those in FBC.
Keywords: Activation energy; Coal; Fluidized bed combustor; Ignition temperature; Thermogravimetric analyzer